Stereotyping criers : the evaluation of crying Individuals across contexts - Low, Nethania Ann Yi Fong (2019)
Crying is an intense emotional expression, and when it occurs in an organization, observers evaluate criers by stereotyping them. This study examined how criers are evaluated across different contexts (work versus public setting), along the dimensions of warmth and competence. A secondary aim of determining the underlying relationships between tears, and warmth and competence perceptions was examined, with the expresser’s perceived sadness, expresser’s intention to manipulate, observer’s willingness to help, observer’s empathy, and observer’s crying proneness as potential mediators. A two-way within-subjects design was utilized for the primary analyses, and results showed that the presence of tears and a public setting were perceived as warmer and less competent relative to the absence of tears and work setting respectively. A mediation study was used to examine the secondary aim. For the effect of presence of tears on warmth perceptions, expresser’s intention to manipulate and observer’s willingness to help fully explained this relationship in a public setting (informal context); and intention to manipulate partially explained in the workplace (formal context). Empathy and crying proneness, though non-significant as mediators, affected the relationships between tears and perceptions of warmth and competence. Finally, I discussed how these findings extended our understanding of the nuanced effect of tears on warmth and competence perceptions across contexts, and the phenomenon of tears as a subset of emotional expression and perception.